Bio-based succinic acid, process for its preparation and its use in the preparation of polyesters
Patent Information
- Application Number
- CN202611398702.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-09
AI Technical Summary
[0007]针对现有生物基丁二酸精制工艺难以同步脱除多种二价金属杂质,导致下游聚酯分子量不足、热稳定性差、易黄变的问题,本发明提供一种生物基丁二酸、其制备方法及其在制备聚酯中的应用
(1)本发明同步限定Ca2+、Mg2+、Zn2+、Cu2+、Mn2+总质量含量≤50ppm、Ca2+、Mg2+、Zn2+三种二价阳离子总质量含量≥10ppm;及各金属单项阈值,可同时抑制碱土金属引发的聚酯分子链封端终止缺陷,以及过渡金属引发的高温热氧降解、物料水解黄变等问题。所得丁二酸纯度≥99.5wt%、酸度可控。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyester preparation technology, specifically relating to a bio-based succinic acid, its preparation method, and its application in polyester preparation. Background Technology
[0002] Fully biodegradable polymer materials have become a core category for replacing traditional petroleum-based plastics. Among them, PBS homopolymer and PBSA copolymer have excellent mechanical toughness, processing adaptability, and fully biodegradable properties, meeting the EN13432 compostability certification requirements. They are widely used in food packaging, biodegradable mulch films, disposable injection molded products, film materials, and other fields, and the market demand continues to grow rapidly.
[0003] Bio-based succinic acid is the core binary monomer for preparing biodegradable polyesters such as PBS / PBSA. Compared to traditional petrochemical-based succinic acid, the bio-fermentation preparation route has advantages such as low carbon emissions, environmental friendliness, renewable raw materials, and low carbon emissions, making it the mainstream development direction of the high-end biodegradable polyester industry. However, during the bio-fermentation process, to maintain cell growth and the acid-base balance of the fermentation system, alkaline regulators need to be continuously added. Simultaneously, factors such as the culture medium raw materials and slight corrosion of the fermentation tank continuously introduce various divalent metal cation impurities into the system, mainly including Ca2+. 2+ Mg 2+ Zn 2+ Cu 2+ Mn 2+ Such trace metal impurities are difficult to completely remove through conventional refining methods, which is the core bottleneck restricting the improvement of the quality of polymer-grade bio-based succinic acid.
[0004] Trace amounts of divalent metal impurities remaining in succinic acid monomers can cause multiple irreversible defects during the high-temperature polymerization of polyester and its subsequent use. Among these, Ca... 2+ Mg 2+ Alkaline earth metals readily combine with the carboxyl groups of succinic acid to form monofunctional metal carboxylates. During the polycondensation reaction, these metals act as chain-sealing agents, significantly blocking polyester chain growth. This results in lower molecular weight and a wider molecular weight distribution in the product, ultimately leading to insufficient mechanical properties of the polyester, failing to meet the production requirements for high-toughness blown film products. Zn 2+ Cu 2+ Mn 2+ Transition metal ions possess redox activity and will continuously catalyze free radical thermo-oxidative degradation reactions during the high-temperature polymerization and long-term storage of polyester at 220-260℃. This will cause polyester chips to yellow and melt stability to decrease, making it impossible to prepare highly transparent food contact grade products. It will also significantly reduce the material's resistance to humid heat aging, leading to rapid degradation of the mechanical properties of mulch films and outdoor packaging products and a significant reduction in shelf life.
[0005] Currently, the industry's conventional bio-based succinic acid refining process mainly employs a purification mode combining solvent extraction and single-stage cation exchange resins. Solvent extraction methods, such as diisooctyl phosphate extraction, have poor selectivity for transition metal ions and struggle to achieve synergistic and deep removal of multiple divalent metal impurities. They can only remove some free alkali and alkaline earth metal impurities from the system, exhibiting extremely poor removal capabilities for protein, peptide complexed metal impurities, and trace transition metal impurities in fermentation systems. Succinic acid products prepared using existing refining processes generally have a high total divalent metal content. When used in polymerization production, this easily leads to batch quality defects such as insufficient polyester polymerization degree, poor thermal retention stability, product yellowing, and hydrolytic failure, severely limiting the stable large-scale production of high-end film-grade, food contact-grade, and high-weather-resistant PBS / PBSA polyesters.
[0006] In summary, developing an integrated green refining process for bio-based succinic acid that can precisely remove multiple types of harmful divalent metal impurities, has controllable impurity indicators, high purity, and stable color and acidity is a crucial technical problem that urgently needs to be solved in this field. This process would systematically address the industry pain points of downstream polyester polymerization limitations, poor thermal stability, and easy yellowing and aging from the raw material end. Summary of the Invention
[0007] To address the problem that existing bio-based succinic acid refining processes struggle to simultaneously remove multiple divalent metal impurities, leading to insufficient molecular weight, poor thermal stability, and easy yellowing in downstream polyesters, this invention provides a bio-based succinic acid, its preparation method, and its application in polyester preparation.
[0008] To solve the above technical problems, the technical solution adopted by the present invention is as follows: This invention provides a bio-based succinic acid, wherein the bio-based succinic acid contains metal ions, and the metal ions include Ca... 2+ Mg 2+ Zn 2+ Cu 2+ Mn 2+ The total mass content of the five divalent cations is ≤50ppm; Unlike existing technologies that only control conventional alkaline earth metal ions, this invention precisely limits Ca... 2+ Mg 2+ Zn 2 + Cu 2+ Mn 2+Five threshold values for the total content of harmful divalent metals were established to specifically constrain transition metal impurities with redox activity and alkaline earth metal impurities that easily cause molecular chain termination. Controlling the total content of these five divalent metal ions to below 50 ppm can simultaneously suppress metal ion-induced polyester molecular chain termination side reactions and high-temperature free radical degradation side reactions, significantly improving the thermal retention stability and mechanical property retention rate of subsequently prepared polyesters, and avoiding problems such as yellowing and hydrolytic failure.
[0009] The bio-based succinic acid contains the following individual mass content of each divalent metal ion: Ca 2+ ≤25ppm, Mg 2+ ≤15ppm, Zn 2+ ≤6ppm, Cu 2+ ≤2ppm, Mn 2+ ≤2ppm; The bio-based succinic acid contains Ca 2+ Mg 2+ Zn 2+ The total mass content of the three ions is ≥10ppm; The bio-based succinic acid has a purity of ≥99.5wt%, meeting the purity requirements of the binary monomers for PBS / PBSA polyester in EN13432 compostable certification.
[0010] Under test conditions of 25°C and an aqueous solution concentration of 0.1 mol / L, the pH of the bio-based succinic acid aqueous solution is ≤2.6.
[0011] An integrated green refining method for low divalent metal bio-based succinic acid includes the following steps: fermentation broth heating and denaturation, ceramic microfiltration, 1000Da ultrafiltration to remove colloidal impurities, three-chamber bipolar membrane BMED treatment, two-stage aminophosphonic acid chelating resin series treatment, weak anion-strong cation mixed ion exchange for deep refining, vacuum concentration, three-stage gradient low-temperature recrystallization, and vacuum drying.
[0012] The fermentation broth pretreatment section includes heating and denaturation of the fermentation broth, ceramic microfiltration, and 1000Da ultrafiltration to remove colloidal impurities; Fermentation broth pretreatment section: The crude succinic acid stock solution prepared by fermentation is heated to 75-85℃ and kept at a constant temperature for 25-35 minutes to allow the bacterial proteins and macromolecular colloids in the stock solution to fully denature and aggregate and precipitate; then it is filtered through a 0.1μm ceramic microfiltration membrane to completely remove the solid residues of the bacterial cells; the filtrate is then deeply filtered through an ultrafiltration membrane with a molecular weight cutoff of 1000Da to remove residual macromolecular peptides and soluble colloidal impurities; The solution is kept at a constant temperature of 75-85℃ for 25-35 minutes, which allows the bacterial proteins and macromolecular colloids in the original solution to be fully denatured and aggregated and precipitated. The 0.1μm ceramic microfiltration membrane completely removes the solid residues of the bacteria. The 1000Da ultrafiltration membrane deeply filters the solution and removes the residual macromolecular peptides and soluble colloidal impurities.
[0013] Three-chamber bipolar membrane BMED treatment section: Employs a three-chamber homogeneous bipolar membrane module (acid chamber-salt chamber-alkali chamber), controlling the operating temperature at 35-45℃ and the current density at 120-160 A / m. 2 ; Two-stage aminophosphonic acid chelating resin tandem treatment process: This section adopts a two-stage aminophosphonic acid chelating resin series process, with the feed liquid flow rate controlled at 0.6-1.0 BV / h throughout the process; the first-stage resin operates normally, and the feed liquid of the first-stage resin is directly taken from the upstream BMED effluent without additional pH adjustment, maintaining the pH environment of the feed liquid; the pH of the feed liquid of the second-stage resin is lowered by 0.4-0.8 pH units, and the second-stage resin adopts a weakly acidic buffer protonation in-situ modification pretreatment process. The aminophosphonic acid chelating resin is selected from either CH-93 or IRC747. The specific modification and recycling process of the secondary resin is as follows: (1) Initialization pretreatment of new resin: After the secondary aminophosphonic acid resin is filled, conventional H-type conversion is performed using 5wt% dilute hydrochloric acid, followed by rinsing with pure water until the pH of the outlet liquid is stable at 4.5-5.5; then acetate-sodium acetate buffer solution is introduced, and the space velocity (SV) is controlled at 1.0-1.5 BV / h, and 2-3 BV buffer solution is continuously introduced; after modification, 1-2 BV of pure water is used for rinsing. The total solute concentration of the acetic acid-sodium acetate buffer solution is 0.15-0.25 mol / L, and the pH value is 4.2-4.8. A brief 1-2 BV pure water rinse only removes free buffer salts within the resin pores, retaining the monoprotonated PO3H on the resin surface. - The active sites are directly incorporated into the adsorption process.
[0014] (2) Periodic cyclic modification and regeneration: After the secondary resin completes 2-3 adsorption-regeneration cycles, it is regenerated with conventional hydrochloric acid and washed with water until the pH of the outlet liquid stabilizes at 4.5-5.5. Then, the above-mentioned acetate-acetate buffer protonation modification and short rinsing process are repeated to maintain the resin's specific adsorption performance.
[0015] This modification process can regulate the protonation state of the functional groups in aminophosphonic acid resin, appropriately retain single protonation sites, and reduce the resin's susceptibility to residual Ca. 2+ Mg 2+ The adsorption of ions enhances the adsorption of Zn. 2+ Cu 2+Mn 2+ It has the ability to selectively capture transition metals; and the trace amounts of acetate that leak out can be completely retained by the subsequent weak anion exchange resin, leaving no impurities or contaminating the finished product.
[0016] Weak anion-strong cation mixed ion exchange deep refining section The feed solution treated with chelating resin is passed into a mixed ion exchange bed filled with weakly basic anion exchange resin and strong acidic cation exchange resin, and the feed solution flow rate is controlled at 0.8-1.2 BV / h. By utilizing the deep adsorption properties of mixed-bed resin, residual trace amounts of complexed divalent metal ions and trace amounts of acetate impurities that have leaked out in the early stages are completely captured in the system.
[0017] Reduced pressure concentration and three-stage gradient low temperature recrystallization section The highly refined pure liquid was concentrated under reduced pressure at 65-75℃ and a vacuum of -0.07 to -0.09 MPa until the succinic acid mass fraction reached 18-22 wt%. Subsequently, a three-stage gradient low-temperature crystallization process was adopted: crystallization at 25℃ for 2 hours, crystallization at 12℃ for 2 hours, and crystallization at 4℃ for 2 hours.
[0018] Taking advantage of the fact that the low-temperature solubility of metal salts is much higher than that of succinic acid, all residual metal impurities are retained in the crystallization mother liquor; the crystallization mother liquor is all recycled back to the BMED feed end for reuse, with no material loss and no wastewater discharge, greatly improving product yield.
[0019] Vacuum drying section The solid crystals after gradient crystallization are dried at a low temperature of 43-47℃ under vacuum to remove surface free water, thus obtaining bio-based succinic acid.
[0020] This invention provides a polyester, wherein the raw material of the polyester includes bio-based succinic acid; The bio-based succinic acid contains metal ions, among which Ca... 2+ Mg 2+ Zn 2+ Cu 2+ Mn 2+ The total mass content of the five divalent cations is ≤50ppm; The bio-based succinic acid contains the following individual mass content of each divalent metal ion: Ca 2+ ≤25ppm, Mg 2+ ≤15ppm, Zn 2+ ≤6ppm, Cu 2+ ≤2ppm, Mn 2+ ≤2ppm.
[0021] The bio-based succinic acid contains Ca 2+ Mg 2+Zn 2+ The total mass content of the three divalent cations is ≥10 ppm; The bio-based succinic acid has a purity of ≥99.5wt%.
[0022] Under test conditions of 25°C and an aqueous solution concentration of 0.1 mol / L, the pH of the bio-based succinic acid aqueous solution is ≤2.6.
[0023] The polyester is a PBS homopolymer or a PBSA copolymer; The raw materials of the polyester include, based on the total molar amount of diacids, the diacid components include the above-mentioned bio-based succinic acid and adipic acid, with a molar ratio of bio-based succinic acid to adipic acid of 65-100:0-35; and the molar ratio of 1,4-butanediol to the total diacids is 1.15-1.5:1.
[0024] The above-mentioned polyester is prepared by mixing bio-based succinic acid, optional adipic acid, 1,4-butanediol, and tetrabutyl titanate, and then carrying out an esterification reaction under a nitrogen protective atmosphere; the esterification temperature is 170-210℃, and the reaction is maintained for 1-4 hours; after esterification, the temperature is raised to carry out pre-condensation for 1.4-2 hours at a pre-condensation temperature of 230-250℃; the temperature is further raised to the final condensation temperature of 240-260℃, the system is evacuated to ≤5mbar, and the final condensation reaction is carried out for 2-3 hours to obtain PBS homopolymer or PBSA copolyester.
[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The present invention simultaneously limits Ca 2+ Mg 2+ Zn 2+ Cu 2+ Mn 2+ Total mass content ≤50ppm, Ca 2+ Mg 2+ Zn 2+ The total mass content of the three divalent cations is ≥10ppm; and the individual threshold values for each metal can simultaneously suppress polyester molecular chain termination defects caused by alkaline earth metals, as well as problems such as high-temperature thermo-oxidative degradation and material hydrolysis and yellowing caused by transition metals. The resulting succinic acid has a purity ≥99.5wt% and its acidity is controllable.
[0026] (2) The total divalent metal content of succinic acid prepared by the method of the present invention is stably controlled between 16.3-42.6 ppm, with low and controllable impurity content. PBS / PBSA polyester prepared based on this raw material can stably obtain 11.6 × 10⁻⁶ ppm. 4 -12.5×10 4High molecular weight (g / mol), narrow molecular weight distribution of 1.72-1.85; initial tensile strength ≥37.8MPa, elongation at break 648-685%, strength retention rate ≥88.4% after 10 min heat retention at 180℃, up to 91.3%; 5% thermogravimetric temperature 333-338℃, yellowness index only 7.9-8.7, clean white chips, excellent resistance to yellowing, stable melt during processing, no broken strip defects, suitable for high-speed blown film and continuous injection molding production.
[0027] (3) This invention employs a BMED-coupled modified chelating resin and a gradient crystallization closed-loop circulation process, which can simultaneously remove free and complexed metal impurities. The process has low reagent consumption, no high-salt wastewater discharge, and high resource utilization rate, making it suitable for large-scale continuous production. The prepared succinic acid can be copolyesterified with different ratios of PBS homopolymer and PBSA, resulting in high-grade products with wide applicability and good market competitiveness and industrialization prospects. Detailed Implementation
[0028] To provide a clearer understanding of the technical features, objectives, and effects of the present invention, specific embodiments of the present invention are now described.
[0029] Example 1 This embodiment provides an integrated green refining method for preparing low divalent metal bio-based succinic acid, including the following steps: (1) Pretreatment of fermentation broth The crude succinic acid stock solution of 80 g / L prepared by fermentation of biomass was heated to 85℃ and kept at a constant temperature for 25 min; then filtered through a 0.1 μm ceramic microfiltration membrane, and the filtrate was further filtered through an ultrafiltration membrane with a molecular weight cutoff of 1000 Da to obtain ultrafiltrate.
[0030] (2) Three-chamber bipolar membrane BMED treatment The ultrafiltrate is fed into the salt chamber of a three-chamber bipolar membrane BMED module, which uses an acid-salt-alkali three-chamber homogeneous bipolar membrane assembly. The operating temperature is controlled at 45℃ and the current density at 160A / m³. 2 .
[0031] (3) Two-stage aminophosphonic acid chelating resin series treatment This section adopts a two-stage aminophosphonic acid chelating resin series process. Both the primary and secondary resins use CH-93. The flow rate of the liquid is controlled at 0.6 BV / h throughout the process, and the primary resin is operated under normal conditions. The secondary resin undergoes a weakly acidic buffer protonation in-situ modification pretreatment process, lowering the feed pH of the secondary resin by 0.8 pH units. The initial pretreatment process for the secondary resin is as follows: After loading, conventional H-type conversion is performed using 5wt% dilute hydrochloric acid, followed by rinsing with pure water until the outlet liquid pH reaches 5.0; an acetate-sodium acetate buffer solution with a total solute concentration of 0.25mol / L and a pH of 4.2 is introduced, controlling the space velocity (SV) at 1.0 BV / h, and continuously introducing 3 BV; after modification, it is rinsed with 1.5 BV of pure water and directly put into adsorption operation.
[0032] (4) Deep purification by mixed ion exchange of weak anion and strong cation The feed solution treated with chelating resin is passed into a mixed ion exchange bed filled with weakly basic anion exchange resin and strong acidic cation exchange resin, and the feed solution flow rate is controlled at 0.8 BV / h.
[0033] (5) Reduced pressure concentration The highly refined pure liquid was concentrated under reduced pressure at 75°C and a vacuum of -0.09 MPa until the succinic acid mass fraction reached 22 wt%.
[0034] (6) Three-level gradient low-temperature recrystallization A three-stage gradient low-temperature crystallization process is adopted: crystallization at 25℃ for 2 hours, crystallization at 12℃ for 2 hours, and crystallization at 4℃ for 2 hours. All crystallization mother liquor is recycled back to the BMED feed end for reuse.
[0035] (7) Vacuum drying The solid crystals after gradient crystallization are dried at 45℃ under low temperature and vacuum to remove surface free water, thus obtaining bio-based succinic acid.
[0036] The succinic acid sample was digested using a USEPA 3052 microwave-assisted acid digester for complete component digestion, followed by quantitative determination of Ca using inductively coupled plasma optical emission spectrometry (ICP-OES). 2+ Mg 2+ Zn 2+ Cu 2+ Mn 2+ The content of five divalent metal ions; the characteristic spectral lines of each element are as follows: Ca 317.9nm, Mg 279.5nm, Zn 213.8nm, Cu 324.7nm, Mn 257.6nm. The detection limit of this detection method for the above metal elements is as low as 0.01ppm.
[0037] The finished product obtained in this embodiment was tested and found to contain a total content of 16.3 ppm of the five divalent metals, specifically Ca. 2+ 7.5ppm, Mg 2+ 4.2ppm, Zn 2+ 2.4ppm, Cu2+ 1.0ppm, Mn 2+ 1.2 ppm. Succinic acid purity 99.7 wt%, pH value of 0.1 mol / L aqueous solution at 25℃ is 2.45.
[0038] Example 2 This embodiment provides an integrated green refining method for preparing low divalent metal bio-based succinic acid, including the following steps: (1) Pretreatment of fermentation broth The crude succinic acid stock solution of 80 g / L prepared by fermentation of biomass was heated to 80℃ and kept at a constant temperature for 30 min; then filtered through a 0.1 μm ceramic microfiltration membrane; the filtrate was then further filtered through an ultrafiltration membrane with a molecular weight cutoff of 1000 Da.
[0039] (2) Three-chamber bipolar membrane BMED treatment The ultrafiltrate is fed into the salt chamber of a three-chamber bipolar membrane BMED, using a homogeneous three-chamber bipolar membrane module with acid, salt, and alkali chambers, and the operating temperature is controlled at 40℃ and the current density at 140A / m³. 2 .
[0040] (3) Two-stage aminophosphonic acid chelating resin series treatment A two-stage aminophosphonic acid chelating resin series process was adopted. Both the primary and secondary resins were CH-93. The feed flow rate was controlled at 0.8 BV / h throughout the process, and the primary resin was operated under normal conditions. The secondary resin undergoes a weakly acidic buffer protonation in-situ modification pretreatment process, lowering the feed pH of the secondary resin by 0.6 pH units. The initial pretreatment process for the secondary resin involves: conventional H-type conversion using 5wt% dilute hydrochloric acid, followed by rinsing with pure water until the outlet liquid pH stabilizes at 4.5; then, an acetate-sodium acetate buffer solution with a total solute concentration of 0.20 mol / L and a pH of 4.5 is introduced, with a space velocity (SV) controlled at 1.2 BV / h, continuously introduced at 2.5 BV; after modification, the resin is rinsed with 1.5 BV of pure water and directly put into adsorption operation.
[0041] (4) Deep purification by mixed ion exchange of weak anion and strong cation The liquid feed is introduced into the mixed bed, and the flow rate is controlled at 1.0 BV / h.
[0042] (5) Reduced pressure concentration The succinic acid was concentrated under reduced pressure at 70°C and a vacuum of -0.085 MPa until the mass fraction of succinic acid reached 20 wt%.
[0043] (6) Three-level gradient low-temperature recrystallization Three-stage gradient low-temperature crystallization process: crystallization at 25℃ for 2 hours, crystallization at 12℃ for 2 hours, and crystallization at 4℃ for 2 hours.
[0044] (7) Vacuum drying Low-temperature vacuum drying at 43℃ yields bio-based succinic acid.
[0045] Following the detection method for metal ions in the succinic acid sample in Example 1, the finished product obtained in this example was tested, and the total content of the five divalent metals in the finished product was 30.3 ppm, specifically Ca. 2+ 13.6 ppm, Mg 2+ 9.0 ppm, Zn 2+ 4.6ppm, Cu 2+ 1.5ppm, Mn 2+ 1.6 ppm. Succinic acid purity 99.6 wt%, pH value of 0.1 mol / L aqueous solution at 25℃ is 2.52.
[0046] Example 3 This embodiment provides an integrated green refining method for preparing low divalent metal bio-based succinic acid, including the following steps: (1) Pretreatment of fermentation broth The crude succinic acid stock solution of 80 g / L prepared by fermentation of biomass was heated to 75°C and kept at a constant temperature for 35 min; then filtered through a 0.1 μm ceramic microfiltration membrane; the filtrate was then further filtered through an ultrafiltration membrane with a molecular weight cutoff of 1000 Da.
[0047] (2) Three-chamber bipolar membrane BMED treatment The ultrafiltrate is fed into the salt chamber of a three-chamber bipolar membrane BMED module, which uses an acid-salt-alkali three-chamber homogeneous bipolar membrane assembly. The operating temperature is controlled at 35℃ and the current density at 120A / m³. 2 .
[0048] (3) Two-stage aminophosphonic acid chelating resin series treatment A two-stage aminophosphonic acid chelating resin series process was adopted. Both the primary and secondary resins were IRC747. The feed flow rate was controlled at 1.0 BV / h throughout the process, and the primary resin was operated under normal conditions. The secondary resin undergoes a weakly acidic buffer protonation in-situ modification pretreatment process, lowering the feed pH of the secondary resin by 0.4 pH units. The initial pretreatment process for the secondary resin involves: conventional H-type conversion using 5wt% dilute hydrochloric acid, followed by rinsing with pure water until the outlet liquid pH stabilizes at 5.5; then, an acetate-sodium acetate buffer solution with a total solute concentration of 0.16 mol / L and a pH of 4.75 is introduced, with a space velocity (SV) controlled at 1.5 BV / h, continuously introduced at 2 BV; after modification, the resin is rinsed with 1 BV of pure water and directly put into adsorption operation.
[0049] (4) Deep purification by mixed ion exchange of weak anion and strong cation The liquid feed is introduced into the mixed bed, and the flow rate is controlled at 1.2 BV / h.
[0050] (5) Reduced pressure concentration The succinic acid was concentrated under reduced pressure at 68°C and a vacuum of -0.075 MPa until the mass fraction of succinic acid reached 18 wt%.
[0051] (6) Three-level gradient low-temperature recrystallization Three-stage gradient low-temperature crystallization process: crystallization at 25℃ for 2 hours, crystallization at 12℃ for 2 hours, and crystallization at 4℃ for 2 hours.
[0052] (7) Vacuum drying The bio-based succinic acid product was obtained by vacuum drying at 47℃.
[0053] Following the detection method for metal ions in the succinic acid sample in Example 1, the finished product obtained in this example was tested. The total content of the five divalent metals in the finished product was 42.6 ppm, of which Ca... 2+ 21.1 ppm, Mg 2+ 13.5ppm, Zn 2+ 4.7ppm, Cu 2+ 1.7ppm, Mn 2+ 1.6 ppm. Succinic acid purity 99.5 wt%, pH value of 0.1 mol / L aqueous solution at 25℃ is 2.58.
[0054] Comparative Example 1 Comparative Example 1 adopts the integrated green refining method for low divalent metal bio-based succinic acid as described in Example 2. In step (3), after the two-stage aminophosphonic acid chelating resin is loaded, only 5wt% dilute hydrochloric acid is used for conventional H-type conversion. After rinsing with pure water until the pH of the outlet liquid stabilizes at 4.5, it is directly put into adsorption operation without undergoing modification treatment with acetic acid-sodium acetate buffer solution. The remaining steps and process parameters are the same as in Example 2.
[0055] Following the detection method for metal ions in the succinic acid sample in Example 1, the finished product obtained in this comparative example was tested. The total content of the five divalent metals in the finished product was 33.4 ppm, specifically Ca... 2+ 10.3 ppm, Mg 2+ 8.2ppm, Zn 2+ 6.8ppm, Cu 2+ 3.8ppm, Mn 2+ 4.3 ppm. Succinic acid purity 99.3 wt%, pH value of 0.1 mol / L aqueous solution at 25℃ is 2.48.
[0056] Comparative Example 2 Comparative Example 2 adopts the integrated green refining preparation method of low divalent metal bio-based succinic acid in Example 2. In the two-stage aminophosphonic acid chelating resin series treatment in step (3), the pH of the secondary resin feed is not adjusted, and the original pH value of the upstream effluent is directly used for the feed. The remaining steps and process parameters are the same as in Example 2.
[0057] Following the detection method for metal ions in the succinic acid sample in Example 1, the finished product obtained in this comparative example was tested. The total content of the five divalent metals in the finished product was 26.6 ppm, specifically Ca... 2+ 10.9 ppm, Mg 2+ 5.5ppm, Zn 2+ 5.2ppm, Cu 2+ 2.7ppm, Mn 2+ 2.3 ppm. Succinic acid purity 99.5 wt%, pH value of 0.1 mol / L aqueous solution at 25℃ is 2.59.
[0058] Comparative Example 3 This comparative example provides a method for preparing bio-based succinic acid, specifically including the following steps: (1) After filtering the 80 g / L crude succinic acid stock solution prepared by fermentation of biomass, 50 g of diisooctyl phosphate was added to the succinic acid stock solution for 8 stages of forward cross-current extraction to obtain the succinic acid-loaded organic phase. Then, the succinic acid-loaded organic phase was subjected to 5 stages of reverse cross-current extraction with 85 g of deionized water to obtain the succinic acid aqueous solution. (2) Pass the succinic acid aqueous solution obtained in step (1) through a cation exchange resin column at a flow rate of 1 BV / h, and elute with water at a mass of 6 times that of the succinic acid aqueous solution to obtain succinic acid effluent. (3) The succinic acid effluent obtained in step (2) is decolorized with activated carbon at 75°C for 60 min. The activated carbon has a mass of 8 g based on a volume of 1 L of succinic acid effluent. Then, it is filtered at 50°C using an ultrafiltration membrane with a pore size of 40 nm to obtain succinic acid filtrate. (4) The succinic acid filtrate obtained in step (3) is subjected to vacuum distillation. The distillation temperature is controlled at 70℃ and the pressure is -0.08MPa. When the succinic acid content is greater than 15wt%, the distillation is stopped. The concentrated succinic acid solution is placed at a low temperature (4℃) for cooling and crystallization to obtain white succinic acid crystals, which is the bio-based succinic acid product.
[0059] Following the detection method for metal ions in the succinic acid sample in Example 1, the finished product obtained in this comparative example was tested. The total content of the five divalent metals in the finished product was 65.3 ppm, specifically Ca... 2+ 25.4 ppm, Mg2+ 7.8ppm, Zn 2+ 18.5ppm, Cu 2+ 6.4ppm, Mn 2+ 7.2 ppm. Succinic acid purity 98.6 wt%, pH value of 0.1 mol / L aqueous solution at 25℃ is 2.74.
[0060] Comparative Example 4 Comparative Example 4 adopted the integrated green refining method for low divalent metal bio-based succinic acid in Example 1, changing the two-stage aminophosphonic acid chelating resin series treatment in step (3) to a four-stage aminophosphonic acid chelating resin series treatment. An additional aminophosphonic acid chelating resin was added before and after the two-stage aminophosphonic acid chelating resin series treatment in step (3) of Example 1. The first-stage aminophosphonic acid chelating resin added earlier was operated normally, while the aminophosphonic acid chelating resin added later adopted the same weakly acidic buffer protonation in-situ modification pretreatment process as in step (3) of Example 1. The remaining steps and process parameters were the same as in Example 1.
[0061] Following the detection method for metal ions in the succinic acid sample in Example 1, the finished product obtained in this comparative example was tested. The total content of the five divalent metals in the finished product was 6.9 ppm, specifically Ca... 2+ 3.3ppm, Mg 2+ 2.1ppm, Zn 2+ 1.0ppm, Cu 2+ 0.3ppm, Mn 2+ 0.2 ppm. Succinic acid purity 99.7 wt%, pH value of 0.1 mol / L aqueous solution at 25℃ is 2.45.
[0062] Application Example 1 In this application example, the ultra-low metal bio-based succinic acid prepared in Example 1 is used as the sole dicarboxylic acid raw material (100 mol% succinic acid, 0 mol% adipic acid); the total molar ratio of 1,4-butanediol to dicarboxylic acid is 1.15:1.
[0063] Polyester preparation method: Bio-based succinic acid, 1,4-butanediol and tetrabutyl titanate were added to a polymerization reactor under nitrogen protection; the esterification temperature was 170℃ and the temperature was maintained for 4 hours; after esterification, the temperature was raised to 230℃ for pre-condensation for 2 hours; the temperature was further raised to 240℃ and the vacuum of the system was controlled at ≤5mbar for final condensation for 3 hours to obtain high-purity PBS homopolymer polyester.
[0064] Application Example 2 This application example uses low-metal bio-based succinic acid prepared in Example 2 as a dicarboxylic acid raw material; the molar ratio of dicarboxylic acid is: 80 mol% bio-based succinic acid and 20 mol% adipic acid; the molar ratio of 1,4-butanediol to the total dicarboxylic acid is 1.3:1.
[0065] Polyester preparation method: Bio-based succinic acid, adipic acid, 1,4-butanediol, and tetrabutyl titanate were added to a polymerization reactor under nitrogen protection; the esterification temperature was 190℃ and the temperature was maintained for 2.5h; after esterification, the temperature was raised to 240℃ for pre-condensation for 1.7h; the temperature was further raised to 250℃ and the system vacuum was ≤5mbar for final condensation for 2.5h to obtain PBSA copolyester.
[0066] Application Example 3 In this application example, the critically qualified low-metal bio-based succinic acid prepared in Example 3 is used as the dicarboxylic acid raw material; the molar ratio of dicarboxylic acid is: 65 mol% bio-based succinic acid and 35 mol% adipic acid; the molar ratio of 1,4-butanediol to the total dicarboxylic acid is 1.5:1.
[0067] Polyester preparation method: Bio-based succinic acid, adipic acid, 1,4-butanediol and tetrabutyl titanate are added to a polymerization reactor under nitrogen protection; esterification temperature is 210℃ and held for 1 hour; after esterification, the temperature is raised to 250℃ for pre-condensation for 1.4 hours; the temperature is further raised to 260℃ and the system vacuum is ≤5mbar for final condensation for 2 hours to obtain a highly flexible PBSA copolyester.
[0068] Application Example 4 This application example, based on the bio-based succinic acid obtained in Example 2, precisely regulates Zn by adding exogenous zinc salt. 2+ The content was reduced to 12 ppm, while the other metal indicators, purity, and acidity remained unchanged; the polymerization process and raw material ratio were completely identical to the intermediate reference process in Application Example 2.
[0069] Raw material pretreatment: Take the bio-based succinic acid product obtained in Example 2, uniformly dope it with a trace amount of zinc succinate, and test to confirm the finished product Zn. 2+ The concentration was 12 ppm, while other indicators remained unchanged. Subsequently, PBSA copolyester was prepared using the 80:20 dicarboxylic acid ratio, 1.3:1 alcohol-acid ratio, and three-stage polymerization process of Application Example 2.
[0070] Application Example 5 In this application example, succinic acid prepared in Comparative Example 1 was used as a dicarboxylic acid raw material. The polyester preparation process adopted the standard intermediate polymerization process and ratio of Application Example 2 without any parameter changes, and PBSA copolyester was prepared.
[0071] Application Example 6 This comparative application example uses succinic acid prepared in Comparative Example 2 as a dicarboxylic acid raw material. The polyester preparation process adopts the standard intermediate polymerization process and ratio of Application Example 2 throughout the process to prepare PBSA copolyester.
[0072] Application Example 7 In this comparative application example, succinic acid prepared in Comparative Example 3 was used as the dicarboxylic acid raw material. The polyester preparation process adopted the standard intermediate polymerization process and ratio of Application Example 2 throughout the process, and PBSA copolyester was prepared.
[0073] Application Example 8 This application example, based on the bio-based succinic acid obtained in Example 2, precisely regulates the Ca2+ levels by adding exogenous calcium and magnesium salts. 2+ 50ppm, Mg 2+ 30ppm, while other metal indicators, purity, and acidity remain unchanged; the polymerization process and raw material ratio are completely identical to the intermediate reference process in Application Example 2.
[0074] Raw material pretreatment: The bio-based succinic acid product obtained in Example 2 was uniformly doped with trace amounts of calcium succinate and magnesium succinate. The Ca content of the finished product was tested and confirmed. 2+ 50ppm, Mg 2+ 30 ppm, with other indicators remaining unchanged; subsequently, PBSA copolyester was prepared using the 80:20 dicarboxylic acid ratio, 1.3:1 alcohol-acid ratio, and three-stage polymerization process of Application Example 2.
[0075] Application Example 9 In this comparative application example, succinic acid prepared in Comparative Example 4 was used as the dicarboxylic acid raw material. The polyester preparation process adopted the standard intermediate polymerization process and ratio of Application Example 2 throughout the process, and PBSA copolyester was prepared.
[0076] Application Example 10 This application example, based on the bio-based succinic acid obtained in Comparative Example 4, precisely controls the Cu content in the bio-based succinic acid by adding exogenous copper and manganese salts. 2+ 1.0ppm, Mn 2+ 1.2 ppm, while other metal indicators, purity, and acidity remained unchanged; the polymerization process and raw material ratio were completely identical to the intermediate reference process in Application Example 2.
[0077] Application Example 11 This application example, based on the bio-based succinic acid obtained in Comparative Example 4, precisely regulates the Ca content in the bio-based succinic acid by adding exogenous calcium, magnesium, and zinc salts. 2+ 7.5ppm, Mg 2+ 4.2ppm, Zn 2+ The concentration was 2.4 ppm, while the other metal indicators, purity, and acidity remained unchanged; the polymerization process and raw material ratio were completely identical to the intermediate reference process in Example 2.
[0078] Application Example 12 This application example, based on the bio-based succinic acid obtained in Comparative Example 4, precisely regulates the Ca content in the bio-based succinic acid by exogenously adding calcium, magnesium, zinc, copper, and manganese salts. 2+ 5.5ppm, Mg 2+3.5ppm, Zn 2+ 1.8ppm, Cu 2+ 1.0ppm, Mn 2+ 1.2 ppm, with the remaining purity and acidity remaining unchanged; the polymerization process and raw material ratio are completely identical to the intermediate reference process in Application Example 2.
[0079] Application Example 13 This application example, based on the bio-based succinic acid obtained in Comparative Example 4, precisely regulates the Ca content in the bio-based succinic acid by exogenously adding calcium, magnesium, zinc, copper, and manganese salts. 2+ 4.9ppm, Mg 2+ 2.8ppm, Zn 2+ 1.5ppm, Cu 2+ 1.0ppm, Mn 2+ 1.2 ppm, with the remaining purity and acidity remaining unchanged; the polymerization process and raw material ratio are completely identical to the intermediate reference process in Application Example 2.
[0080] Detection Example 1 For the polyesters prepared in corresponding examples 1-13, the weight-average molecular weight, molecular weight distribution (PDI), melt index at 190℃ / 2.16kg, initial tensile strength, elongation at break, tensile strength retention rate at 180℃ for 10 min, yellowness index, and 5% thermal weight loss temperature were tested; the test results are shown in Table 1.
[0081] The weight-average molecular weight (Mw), number-average molecular weight (Mn), and molecular weight distribution index of polyester were determined according to ISO 16014 Gel permeation chromatography (GPC / SEC). The melt flow rate (melt index) of polyester was tested according to ISO 1133 standard, and the test conditions were 190℃ and 2.16kg standard weight. Polyester tensile strength and elongation at break were tested according to ISO 527 standard. The yellowness index of polyester was tested according to the HG / T 3862-2006 standard; the high-temperature thermal retention mechanical properties of polyester were tested using a constant temperature melt retention accelerated aging process at 180℃ for 10 minutes, and the tensile strength retention rate before and after aging was tested. The 5% thermogravimetric temperature was tested according to the ISO 11358-1 thermogravimetric analysis standard, under a nitrogen atmosphere and a heating rate of 10℃ / min. The temperature corresponding to a 5% loss of sample mass was taken as the 5% thermogravimetric temperature.
[0082] Table 1: Polyester Performance Test Data
[0083] As shown in Table 1, the content of five types of divalent metal impurities in bio-based succinic acid raw materials is significantly correlated with the molecular weight, mechanical strength, high-temperature thermal stability, and anti-yellowing properties of polyester polymers.
[0084] Application Examples 1-3 are polyester samples prepared from low-metal succinic acid as described in Examples 1-3 of this invention. The total content of the five divalent metals in the succinic acid raw material was controlled between 16.3-42.6 ppm, and all individual metal ions fell within the index range defined by this invention. All three groups of samples yielded a weight-average molecular weight of 11.6-12.4 × 10⁻⁶. 4 This invention describes a high molecular weight, narrowly distributed polyester with a g / mol PDI of 1.72-1.85; it also exhibits high tensile strength and high elongation at break, high mechanical retention after 180°C heat retention, a 5% thermogravimetric loss temperature in the range of 333-338°C, low yellowness index, and good chip color. This demonstrates that within the metal ion index range defined in this invention, both PBS homopolymer polyester and PBSA copolyesters with different ratios can yield polyester materials that meet the requirements for high-end biodegradable products used in film and injection molding.
[0085] Application Example 4 is for improving Zn only through external sources. 2+ In the experimental group with a zinc content of 12 ppm, other metals such as calcium and magnesium remained at acceptable levels. Under the condition that only the transition metal zinc exceeded the standard, the polyester weight-average molecular weight decreased significantly, the elongation at break decreased significantly, and most notably, the heat retention strength retention rate decreased, the yellowness index increased significantly, and the 5% thermal weight loss temperature decreased significantly. This indicates that Zn... 2+ These transition metal impurities play a key catalytic role in the high-temperature thermo-oxidative degradation and yellowing of polyester. Even if alkaline earth metals are controlled within acceptable limits, excessive transition metals will still seriously damage the thermal processing stability and appearance quality of polyester.
[0086] Application Examples 5 and 6 correspond to the conditions where the secondary resin is not modified with an acetate-acetate buffer and the secondary resin is not adjusted for feed pH, respectively. Both are polyesters prepared from succinic acid obtained by the purification process of this invention, which lacks a key modification step. Compared with the complete process group in Application Example 2, the Zn content in the succinic acid of both groups of samples... 2+ Cu 2+ Mn 2+ The deterioration in transition metal ion removal is reflected in polyester properties, manifesting as a decrease in weight-average molecular weight, elongation at break, heat retention rate, thermogravimetric temperature, and an increase in yellowness index. In Example 5, where buffer modification was completely eliminated, the performance degradation was greater than in Example 6, where only pH adjustment was eliminated. This demonstrates that the protonation buffer modification of the secondary resin, in conjunction with feed pH regulation, is crucial for improving Zn removal efficiency. 2+ Cu 2+ Mn 2+Selective adsorption and reduction of transition metal content in the finished product are key process steps. Without this modification step, it is impossible to stably obtain high-performance polyester monomers.
[0087] Application Example 7 describes the preparation of polyester from succinic acid using a traditional extraction and single-stage cation exchange process. This process cannot effectively remove complexed divalent metal ions, resulting in a high total content of five types of divalent metals in the finished product, with transition metal impurities being particularly prominent. The resulting polyester also exhibits multiple defects, including low molecular weight, decreased toughness, poor thermal stability, and severe yellowing, failing to meet the processing and use requirements of high-end films and food contact products.
[0088] Application Example 8 is for Ca only 2+ Mg 2+ The experimental group with excessive alkaline earth metal ions, Zn 2+ Cu 2+ Mn 2+ The transition metals remain within the acceptable range defined in this invention. As can be seen from the data, Ca... 2+ Mg 2+ Exceeding the standard will significantly exert the chain-end effect, and the weight-average molecular weight of polyester will decrease significantly to 7.5×10. 4 The molecular weight distribution broadened to 2.25 g / mol, the elongation at break dropped significantly to 332%, the tensile strength declined significantly, and the melt index increased significantly. However, due to the low content of transition metal impurities, the polyester's 5% thermal weight loss temperature, thermal retention strength retention rate, and yellowing index deteriorated to a limited extent, and the thermo-oxidative degradation and yellowing phenomena were not prominent.
[0089] In Application Example 9, the succinic acid product used had all metal ions at extremely low levels, including Ca. 2+ Mg 2+ Zn 2+ The total content is far below the lower limit of 10 ppm, Cu 2+ Mn 2+ Approaching trace levels. The weight-average molecular weight of polyester decreased to 9.7 × 10⁻⁶. 4 The molecular weight distribution broadened to 1.94, the melt index increased to 6.3 g / 10 min, and the elongation at break dropped sharply to 526%, resulting in significant deterioration of mechanical properties; however, the yellowness index, thermal weight loss temperature, and thermal retention rate did not deteriorate significantly, and the thermal stability and color performance were excellent.
[0090] Application Example 10: Ca in succinic acid finished product 2+ Mg 2+ Zn 2+ Based on an extremely low mass content, only exogenous Cu 2+ Mn 2+The concentration was adjusted to that of Application Example 1. Compared with Application Example 1, and in conjunction with a horizontal comparison with Application Example 9, it can be seen that the polymerization and mechanical properties of polyester, such as molecular weight, tensile strength, elongation at break, and melt index, are basically the same as those of Application Example 9. However, the yellowness index, thermal weight loss temperature, and thermal retention rate do not show significant deterioration, and the thermal stability and color performance are excellent.
[0091] Application Example 11 uses succinic acid in the finished product containing Ca. 2+ Mg 2+ Zn 2+ Adjusted to the range of this invention, Cu 2+ Mn 2+ Maintaining trace amounts. Compared to Application Example 9, the polyester weight-average molecular weight rebounded, the molecular weight distribution narrowed, tensile strength and elongation at break recovered and improved, the melt index decreased, and polymerization and mechanical properties were restored. Simultaneously, due to the regular molecular chain structure, the heat retention rate, yellowness index, and 5% thermogravimetric temperature exhibited excellent performance. Overall data were comparable to Application Example 1.
[0092] Application Example 12 uses succinic acid in the finished product containing Ca. 2+ Mg 2+ Zn 2+ The total mass content was 10.8 ppm. Compared with Application Example 1, the polymerization and mechanical properties were generally comparable; the thermal stability and yellowness fluctuated only slightly.
[0093] Application Example 13 uses succinic acid in the finished product containing Ca. 2+ Mg 2+ Zn 2+ The total mass content was 9.2 ppm. Compared with Application Example 1, the molecular weight and mechanical properties decreased, the heat retention rate decreased, the yellowness index increased, and the 5% thermal weight loss temperature decreased slightly.
[0094] As can be seen from application example 9-13, Ca 2+ Mg 2+ Zn 2+ Insufficient content, Ca 2+ Mg 2+ Zn 2+ When the total mass content of the three substances is <10ppm, it will result in a lower molecular weight of polyester, worse mechanical properties, and more structural defects in the molecular chain; Cu 2+ Mn 2+ When all are ≤2ppm, even if Cu 2+ 0.3ppm, Mn 2+ At 0.2 ppm, it does not affect the polymerization chain growth and mechanical properties; As can be seen from application examples 1-8, Cu 2+ >2ppm, Mn 2+At concentrations greater than 2 ppm, it can catalyze thermo-oxidative degradation and induce yellowing.
[0095] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A bio-based succinic acid, characterized in that, The bio-based succinic acid contains metal ions, among which Ca... 2+ Mg 2+ Zn 2+ Cu 2+ Mn 2+ The total mass content of the five divalent cations is ≤50ppm; The bio-based succinic acid contains the following individual mass content of each divalent metal ion: Ca 2+ ≤25ppm, Mg 2+ ≤15ppm, Zn 2+ ≤6ppm, Cu 2+ ≤2ppm, Mn 2+ ≤2ppm; The bio-based succinic acid contains Ca 2+ Mg 2+ Zn 2+ The total mass content of the three ions is ≥10ppm.
2. The bio-based succinic acid according to claim 1, characterized in that, Under test conditions of 25°C and an aqueous solution concentration of 0.1 mol / L, the pH of the bio-based succinic acid aqueous solution is ≤2.
6.
3. The method for preparing bio-based succinic acid according to any one of claims 1-2, characterized in that, Includes the following steps: Fermentation broth denaturation by heating, ceramic microfiltration, 1000Da ultrafiltration to remove colloidal impurities, three-chamber bipolar membrane BMED treatment, two-stage aminophosphonic acid chelating resin series treatment, weak anion-strong cation mixed ion exchange for deep purification, vacuum concentration, three-stage gradient low temperature recrystallization, and vacuum drying. The specific operation of the two-stage aminophosphonic acid chelating resin series treatment is as follows: a two-stage aminophosphonic acid chelating resin series process is adopted, and the feed liquid flow rate is controlled at 0.6-1.0 BV / h throughout the process; the first-stage resin is operated normally, and the feed liquid of the first-stage resin is directly adopted from the upstream BMED effluent without additional pH adjustment to maintain the pH environment of the raw material liquid; the pH of the feed liquid of the second-stage resin is lowered by 0.4-0.8 pH units, and the second-stage resin adopts a weakly acidic buffer protonation in-situ modification pretreatment process. The specific modification and recycling process of the secondary resin is as follows: (1) Initialization pretreatment of new resin: After the secondary aminophosphonic acid resin is filled, conventional H-type conversion is performed using 5wt% dilute hydrochloric acid, followed by rinsing with pure water until the pH of the outlet liquid is stable at 4.5-5.5; then acetate-sodium acetate buffer solution is introduced, and the space velocity (SV) is controlled at 1.0-1.5 BV / h, and 2-3 BV buffer solution is continuously introduced; after modification, 1-2 BV of pure water is used for rinsing. The total solute concentration of the acetic acid-sodium acetate buffer solution is 0.15-0.25 mol / L, and the pH value is 4.2-4.
8. (2) Periodic cyclic modification and regeneration: After the secondary resin completes 2-3 adsorption-regeneration cycles, it is regenerated with conventional hydrochloric acid and washed with water until the pH of the outlet liquid stabilizes at 4.5-5.
5. Then, the above-mentioned acetate-acetate buffer protonation modification and short rinsing process are repeated to maintain the resin's specific adsorption performance.
4. The method for preparing bio-based succinic acid according to claim 3, characterized in that, The specific operation of the fermentation stock solution for heating and denaturation, ceramic microfiltration, and 1000Da ultrafiltration to remove colloidal impurities is as follows: the crude succinic acid stock solution prepared by fermentation is heated to 75-85℃ and kept at a constant temperature for 25-35 minutes, then filtered through a 0.1μm ceramic microfiltration membrane, and the filtrate is then deeply filtered through an ultrafiltration membrane with a molecular weight cutoff of 1000Da.
5. The method for preparing bio-based succinic acid according to claim 3, characterized in that, The specific operation of the three-chamber bipolar membrane BMED treatment is as follows: using a three-chamber homogeneous bipolar membrane module with an acid chamber, a salt chamber, and an alkali chamber, controlling the operating temperature at 35-45℃ and the current density at 120-160A / m. 2 .
6. The method for preparing bio-based succinic acid according to claim 3, characterized in that, The specific operation of the weak anion-strong cation mixed ion exchange deep purification is as follows: the feed solution treated with chelating resin is passed into a mixed ion exchange bed filled with weak basic anion resin and strong acid cation resin, and the feed solution flow rate is controlled at 0.8-1.2 BV / h.
7. The method for preparing bio-based succinic acid according to claim 3, characterized in that, The specific operation of the vacuum concentration and three-stage gradient low-temperature recrystallization is as follows: the pure liquid after deep purification by weak anion-strong cation mixed ion exchange is concentrated under vacuum at 65-75℃ and vacuum degree of -0.07 to -0.09MPa until the succinic acid mass fraction reaches 18-22wt%; then a three-stage gradient low-temperature crystallization process is adopted: crystallization at 25℃ for 2h, crystallization at 12℃ for 2h, and crystallization at 4℃ for 2h in sequence.
8. The method for preparing bio-based succinic acid according to claim 3, characterized in that, The specific operation of the vacuum drying is as follows: after gradient crystallization, the solid crystals are dried at a low temperature of 43-47℃ to remove surface free water, thereby obtaining the bio-based succinic acid product.
9. A polyester, characterized in that, The polyester is a PBS homopolymer or a PBSA copolymer, and the raw materials for preparing the polyester include the bio-based succinic acid as described in any one of claims 1-2.
10. A polyester according to claim 9, characterized in that, The raw materials of the polyester include, based on the total molar amount of diacids, bio-based succinic acid and adipic acid, with a molar ratio of 65-100:0-35; and a molar ratio of 1,4-butanediol to the total diacids of 1.15-1.5:1.